Effects of Valproic Acid on Cerebral Nutrient Carriers' Expression in the Rat - Mann Brukner, Aniv; Ben-Hur, Tamir; Honig, Asaf; Ekstein, Dana; Eyal, Sara (Frontiers in Pharmacology, 2018)
Objective: The antiepileptic drug valproate has been shown to affect the expression of carriers for essential compounds and drugs in extracerebral tissues. The aim of the current study was to evaluate in vivo the effect of valproate treatment on the cerebral expression of carriers and selected genes of the blood-brain barrier (BBB) in the rat. Methods: Male Wistar rats were treated daily for seven days by intraperitoneal injections of valproate (75 mg/kg/day, 150 mg/kg/day, or 300 mg/kg/day) or the vehicle. mRNA was isolated from the cerebral cortex and the hippocampus. Transcript levels of 37 genes were measured using a customized gene expression assay. Quantitative histone acetylation was evaluated by western blotting. Glucose6-phosphate (G6P) tissue levels were used as a surrogate of cerebral glucose concentrations. Results: Valproate treatment was associated with significant reduction (up to 22%; P<0.05) in cortical and hippocampal claudin 5-normalized Slc2a1 (Glut1) mRNA expression. G6P levels were not significantly altered, but were correlated with Slc2a1 transcript levels (r=0.499; P<0.02). None of the other 36 screened genes were significantly affected by valproate. Cortical histone hyperacetylation indicated cerebral activity of valproate on a major pathway regulating gene expression (P<0.02). Significance: The effect of valproate on nutrient carriers appears to be tissue-specific and even brain area-specific. If validated in humans, the changes in Glut1 expression might have clinical implications in positron emission tomography imaging. Further studies are required for elucidating the relevance of these findings to the clinic.